Analysis and strategy for improving Indonesian coffee competitiveness in the international market - Budi Rahardjo; Bintang Mukhammad Burhanudin Akbar; Yusuf Iskandar; Anita Shalehah (Universitas Negeri Surabaya, 2020)
In order to face a competitive market environment, knowing the position of the product itself and competitors is needed. Coffee is the main tropical commodity traded in the world. Coffee has great potential and is very competitive. The research objective is to determine the competitiveness of Indonesian coffee and processed coffee beans exports in the international market by using Revealed Comparative Advantage (RCA) to analyze the trade that occurs in several other major exporters such as Brazil, Colombia, and Vietnam as competitors of Indonesian coffee and analyze strategies to increase the competitiveness of Indonesian coffee export in the international market. Indonesia has an average RCA value of 3.64 and is the smallest value compared to other world coffee exporting countries. The small RCA value indicates that Indonesia's comparative advantage still needs to be improved. Based on Export Product Dynamics (EPD), it is known that there are three countries, including Indonesia, which has lost opportunities to be able to trade with other countries, especially coffee products. This condition makes Indonesia needs to improve. Production activities and maintain quality. Indonesian coffee products have a variety of types, which, when used, will increase the competitiveness of the Indonesian state.